Pengaruh Perubahan Organisasi Terhadap Kinerja Pegawai Dengan Komitmen Organisasi Sebagai Variabel Intervening: Studi Kasus di Badan Pendidikan dan Pelatihan Keuangan - Pardomuan Robinson Sihombing; Bungkus Sasongko Purnomo (Program Studi Administrasi Publik Universitas Muhamamdiyah Bengkulu, 2022)
This study aims to determine the effect of organizational change on employee performance with organizational commitment as an intervening variable. The samples in this study were employees at the Financial Education and Training Agency. The analytical method used is a quantitative method using a questionnaire instrument. All indicators used are valid and reliable. The statistical method used to see the effect between variables is linear regression analysis. Based on the results of the study it was concluded that organizational change had a significant positive effect on organizational commitment and employee performance at the Financial Education and Training Agency. Affective commitment has a significant positive effect on employee performance at the Financial Education and Training Agency. Continuance Commitment and Normative Commitment have not significantly affected the performance of employees at the Financial Education and Training Agency. So that when there is an organizational change, this can be used as material for consideration for the leadership on the method of implementing policies that have been set by the organization